The relationship of body condition scores to milk production in dairy buffaloes - Saludes, Thelma A.; Takeshita, Hironobu; Tandang, Abraham G.; Bril, Pinky M.; Bautista, Jose Arceo N. (2021)
A retrospective study of body condition scores (BCS), milk yield, and lactation records of 34 purebreds and crossbred dairy Murrah buffaloes, and climatic parameters were used to determine their relationships with one another. The visual assessments developed for Murrah buffalo was used in BCS determination. Significant correlations (P<0.01) between all parameters except rainfall were found to have weak to moderate monotonic relationships: BCS was negatively correlated to milk yield and affected milk yield by 0.858 kg/day per unit change in BCS. Milk yield was positively affected by early lactation while BCS negatively affected. In early lactation stage, the estimated rate of milk yield increase was 1.519 kg/day and decrease in BCS by 0.267 units. Regarding breed differences, purebred milk yield was positively affected and BCS negatively affected. Purebreds produced significantly more milk (5.44 kg/day) than crossbreds (4.98 kg/day). The highest milk yield was observed both in March for purebreds and crossbreds while, the lowest in August and October for purebreds and crossbreds, respectively. BCS and milk yield were positively correlated with temperature while negatively for relative humidity. In conclusion, BCS, breed, stages of lactation, temperature, and relative humidity have significant effects to milk production.
Keywords: Buffaloes; Milk